O início da docência: vivências, saberes e conflitos de professores de química - Pena, Graziele Borges de Oliveira (2010)
This paper examines the experiences of three teachers of chemistry, early-stage, with less than four years of occupation, or who teach in high school also taught in public schools to state schools in Uberlândia / MG, and aims to study the knowledge and the conflicts that emerge from such experiences. Configures itself as a qualitative case study of ethnographic that used the following methodological tools: interviews, participant observation and document analysis (with emphasis on the memorial). By analyzing the data we seek, first, to reconstruct the life history of the school teachers to see if their experiences as students of elementary school graduation and influence the time of initiation to teaching and how this happens. We also observed the experiences of early career and examining us into the close relationship between knowledge and conflicts. This analysis was divided into two parts: the first relates to the socialization process of teachers in the school community (made up of peers, administration and students) and the second part, the research shifted to understanding the relationship of the teachers with the knowledge of knowledge (content, curriculum and teaching). The reflections made by this research provide contributions to understanding how teachers experience the beginning of his career and stay in teaching as well as the profile and professional identity that will be delineated. Understanding how the teacher starts the profession, their experiences, their relationship with the knowledge necessary for professional practice and the conflicts that emerge from this experience, it helps to uncover a reality that can be better understood, thus facilitating a rapprochement between the world and the academic world of school and also provide ideas that aim to improve the training of teachers of different content, in particular chemistry.